The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1177/1464420720901851
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and numerical investigation of polymethyl methacrylate scaffolds for bone tissue engineering

Abstract: A controversial issue in tissue engineering is the development of new methods to fabricate scaffolds that precisely imitate the structure and function of the extracellular matrix. The objective of this study is to propose a new method in scaffold fabrication and investigate the effects of pore topology, particularly gradient structure, on the mechanical properties of the scaffolds. In this regard, poly(methyl methacrylate) sheets constructing the scaffold's substructures were cut by laser and then stacked on e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…Blends (10 wt%, 15 wt% and 20 wt% bioglass) were prepared using a simple melt blending approach, which did not require the use of hazardous solvents. Moreover, contrary to previously reported studies that investigated simple rectangular and circular scaffold architectures, this research investigated anatomically designed scaffolds with pore size gradients that mimicked the architecture of bone and thus, aimed to improve the overall mechanical behaviour of the scaffolds and thereby making them suitable for load-bearing applications [ 55 , 56 , 57 ].…”
Section: Introductionmentioning
confidence: 99%
“…Blends (10 wt%, 15 wt% and 20 wt% bioglass) were prepared using a simple melt blending approach, which did not require the use of hazardous solvents. Moreover, contrary to previously reported studies that investigated simple rectangular and circular scaffold architectures, this research investigated anatomically designed scaffolds with pore size gradients that mimicked the architecture of bone and thus, aimed to improve the overall mechanical behaviour of the scaffolds and thereby making them suitable for load-bearing applications [ 55 , 56 , 57 ].…”
Section: Introductionmentioning
confidence: 99%
“…The method is based on a tertiary system: solvent (chloroform)-polymer-"no" solvent (methanol), in the correct volume ratio. To achieve the preparation of HCP structures is necessary to immerse the substrate in the prepared solution and then, spontaneously evaporate it in the air [16,[35][36][37]. The advantage of this method, except for the humid environment and other active substances, is the exact ratio of solvents [8].…”
Section: Introductionmentioning
confidence: 99%
“…One possibility is to use polymeric materials, mainly due to their simplicity, flexibility, and low cost compared to other materials, and to prove their usefulness as extracellular matrix (ECM) replacements [38]. These properties and many others such as low density, environmental friendliness, and good physical and mechanical properties have been found in polymethyl methacrylate (PMMA) and its derivatives [35], which have been approved as bioinert and biocompatible polymers used in biomedical applications [36,37,39]. Nanocomposites based on PMMA exhibit excellent results in a body environment and have a protective role against corrosion and, thus, increase the durability of biomedical implants [40].…”
Section: Introductionmentioning
confidence: 99%
“…1 These structures have a variety of applications in different areas, such as lightweight engineering, 2,3 sound and thermal insulation, [4][5][6] impact absorption, 7 and biomaterials. 8,9 Moreover, investigations showed that the mechanical behavior of these lattice structure significantly depends on the micro-structure. 10,11 As a result, a considerable number of studies are focused on the relation between unit cell and mechanical properties of cellular structures.…”
Section: Introductionmentioning
confidence: 99%